Tripartite interaction among teachers, parents and young children in Chinese parent–child program - Kang, Jiali; Bakar, Kamariah Abu; Mohamed, Suziyani (Frontiers in Psychology, 2025)
IntroductionTripartite interaction among teachers, parents, and young children is a cornerstone of early childhood education, especially in China’s parent-child programs designed to support children’s development and enhance parental engagement. Despite their intentions, these interactions often follow rigid patterns, limit children’s agency, and involve minimal communication between adults. This research investigates the dynamics and challenges of such tripartite interactions within Chinese preschools.MethodsA qualitative approach was adopted using purposive sampling in two preschools in Nanjing, China. Participants included 29 children (Mage = 30 months), their parents, and four teachers, engaged in 28 structured parent-child activities. Data collection comprised 1,130 observed tripartite interaction events using event sampling and 23 semi-structured and impromptu interviews with teachers and parents. The data were coded and analyzed in NVivo12 through open, axial, and selective coding to extract interaction types and thematic patterns.ResultsFindings show that adult-initiated interactions (teacher-child-parent and parent-child-teacher types) accounted for 86% of events, primarily reflecting an Initiation-Response-Evaluation (IRE) pattern led by adults. Children’s attempts to initiate were least accepted, indicating a suppression of their subjectivity. Six themes emerged: education and instruction, encouragement and communication, assistance and substitution, guidance through concerns, mutual understanding, and children’s self-expression. A new tripartite interaction model was developed.DiscussionThis research underscores the need for restructuring Chinese parent-child programs by promoting balanced goals, recognizing each party’s role, and cultivating respectful, child-inclusive dialogue to support holistic development.